Teaching the Arabic language and its relationship to developing educational communication skills: An analytical study of some language texts in the third elementary school as a model - Nadjet, Abdellaoui; Alarabi, Dine (Journal of Educational and Psychological Sciences, 2020)
This article aims to effectively invest Arabic language education and develop educational communication skills among learners of the third year of primary education; As the skill of educational communication is the focal point of the educational- learning process and its main axis, This is in view of the fact that teaching Arabic is considered to be an interconnected and coherent unit by the interaction of its communicative elements; Where we chose to define an educational level from the primary stage represented by third- year primary learners as an important stage in the basic education stages and on this basis we were limited to an educational text that includes the six elements of educational communication Through it, we focused on the descriptive analytical approach, in order to highlight the studied code that aims to make the learner the center of the educational- learning process, exchange his knowledge and acquire purposeful communication skills that develop his language and develop his communication competencies.
Keywords: Arabic; educational; communication; educational communication; Primary school learners third year